HUBUNGAN BERAT PLASENTA DENGAN BERAT BADAN DAN PANJANG BADAN BAYI BARU LAHIR - Indryani (LPPM Institut Sains dan Kesehatan Bone, 2021)
Abstract. Birth weight is an indicator of newborn health. The size of birth weight depends on how the intrauterine fetus grows during pregnancy. Babies who are born atherem (37 to 42 weeks) have a normal weight of 2,500 - 4,000 grams. Several factors can affect the birth weight of the baby which consists of factors from the mother, fetal factors, and placenta factors. Placental weight is commonly used to summarize the growth and function of the placenta. This study aimed to analyze the relationship between placental weight and body weight and length of the newborn. This type of research is. analytic survey with cross sectional study design. The number of samples in this study were 30 pregnant women who were taken by total sampling analysis.The results showed that there was a relationship between placental weight with body weight and body length for newborns in Kec. Mare, the data was done by using the chi-squar test, with a confidence level of a = 005. Based on the results of this study, the significance value of birth weight p-value = 0.000 p <0.5, the length of birth body value p-0.00 p> 0 , 5. So it can be concluded that there is a relationship between placental weight and body weight and length of newborns. There is a relationship between placental weight and body weight and length in newborns)